Data from: When Siberia came to the Netherlands: the response of continental black-tailed godwits to a rare spring weather event - Senner, Nathan R.; Verhoeven, Mo A.; Abad-Gómez, José M.; Gutiérrez, Jorge S.; Hooijmeijer, Jos C. E. W.; Kentie, Rosemarie; Masero, José A.; Tibbitts, T. Lee; Piersma, Theunis (Zenodo, 2015)
1. Extreme weather events have the potential to alter both short- and long-term population dynamics as well as community- and ecosystem-level function. Such events are rare and stochastic, making it difficult to fully document how organisms respond to them and predict the repercussions of similar events in the future. 2. To improve our understanding of the mechanisms by which short-term events can incur long-term consequences, we documented the behavioural responses and fitness consequences for a long-distance migratory bird, the continental black-tailed godwit Limosa limosa limosa, resulting from a spring snowstorm and three-week period of record low temperatures. 3. The event caused measurable responses at three spatial scales – continental, regional and local – including migratory delays (+19 days), reverse migrations (>90 km), elevated metabolic costs (+8·8% maintenance metabolic rate) and increased foraging rates (+37%). 4. There were few long-term fitness consequences, however, and subsequent breeding seasons instead witnessed high levels of reproductive success and little evidence of carry-over effects. 5. This suggests that populations with continued access to food, behavioural flexibility and time to dissipate the costs of the event can likely withstand the consequences of an extreme weather event. For populations constrained in one of these respects, though, extreme events may entail extreme ecological consequences. Yearly Black-tailed Godwit Return Rates This data includes data on whether or not an individual godwit that was seen in one year, returned to their breeding grounds the following year. All data is categorized in reference to individual godwits (signified by their Colour Code). The initial year in which an individual was seen is not marked, only the following year is denoted with a 0 (not seen) or a 1 (seen). It also includes a column denoting each molecular individual's sex--0 (unknown), 1 (female), and 2 (male). Yearly Return Rates.xlsx 2013 March-May Resightings of Black-tailed ...